A Low-Carbohydrate Diet Improves Glucose Metabolism in Lean Insulinopenic Akita Mice Along With Sodium-Glucose Cotransporter 2 Inhibitor - Fujita, Yukihiro; Atageldiyeva, Kuralay K.; Takeda, Yasutaka; Yanagimachi, Tsuyoshi; Makino, Yuichi; Haneda, Masakazu (Frontiers in Endocrinology, 2020)
Objective A low-carbohydrate diet (LC) can be beneficial to obese subjects with type2 diabetes mellitus (T2DM). Sodium-glucose cotransporter 2 inhibitor (SGLT2i) presents prompt glucose-lowering effects in subjects with T2DM. We investigated how LC and SGLT2i could similarly or differently influence on the metabolic changes, including glucose, lipid, and ketone metabolism in lean insulinopenic Akita mice. We also examined the impacts of the combination. Methods Male Akita mice were fed ad libitum normal-carbohydrate diet (NC) as a control or low-carbohydrate diet (LC) as an intervention for 8 weeks with or without SGLT2i treatment. Body weight and casual bold glucose levels were monitored during the study, in addition to measuring TG, NEFA, and ketone levels. We quantified gene expressions involved in gluconeogenesis, lipid metabolism and ketogenesis in the liver and the kidney. We also investigated the immunostaining analysis of pancreatic islets to assess the effect of islet protection. Results Both LC and SGLT2i treatment reduced chronic hyperglycemia. Moreover, the combination therapy additionally ameliorated glycemic levels and preserved the islet morphology in part. LC but not SGLT2i increased body weight accompanied by epididymal fat accumulation. In contrast, SGLT2i, not LC potentiated four-fold ketone production with higher ketogenic gene expression, in comparison with the non-treated Akita mice. Besides, the combination did not enhance further ketone production compared to the SGLT2i alone. Conclusions Our results indicated that both LC and SGLT2i reduced chronic hyperglycemia, and the combination presented synergistic favorable effects concomitantly with amelioration of islet morphology, while the combination did not enhance further ketosis in Akita mice.